Perancangan Ulang Tata Letak Toko Ritel Cahaya Abadi Dengan Pendekatan Activity Relationship Chart (ARC) (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2024)
Indonesia has quite rapid development of the retail business. This requires actors who have retail businesses to be involved in consumer purchasing decisions. There are several factors that influence consumer purchasing decisions, one of which is a good and strategic layout of facilities. Cahaya Abadi is a shop that runs a retail business. Cahaya Abadi Store provides various products for daily consumer needs. This research was conducted using the Activity Relationship Chart (ARC) method and Total Closeness Rating (TCR) calculations in data processing. The research uses the Activity Relationship Chart (ARC) method and Total Closeness Rating (TCR) calculations. This research uses primary and secondary data and the methods used are qualitative and quantitative methods. The layout is based on providing convenience for consumers in shopping and it is hoped that consumers will have an efficient and effective time in shopping.